Influence of IL-10RA and IL-22 polymorphisms on outcome of hepatitis C virus infection. - Hennig, B; Frodsham, A; Hellier, S; Knapp, S; Yee, L; Wright, M; Zhang, L; Thomas, H; Thursz, M; Hill, A (2007)
BACKGROUND: Two receptor chains, IL-10RA and IL-10RB, are known to mediate the functions of interleukin-10 (IL-10), which has been shown to be involved in the progression of persistent hepatitis C virus (HCV) infection. Little information is available on the role of host genetic variation in IL-10 receptor genes and outcome of HCV infection. IL-22, an IL-10 homologue, shares the IL-10RB receptor chain with IL-10 and has antiviral properties. We investigated the possible role of polymorphisms in the IL-10RA and IL-22 genes in hepatitis C disease pathogenesis. METHODS: This study population consisted of 631 HCV patients, recruited from several hepatology clinics across Europe. We genotyped four single-nucleotide polymorphisms (SNPs) in the IL-10RA and six SNPs in the IL-22 gene by ligation detection reaction or restriction fragment length polymorphism. Outcome of HCV infection was assessed according to viral clearance, treatment response, severity of fibrosis and overall inflammation. CONCLUSIONS: Variation in IL-10RA appeared to be correlated with response to treatment and inflammation. Two SNPs in IL-22 affected treatment response and viral clearance respectively. We furthermore report on allele and haplotype frequencies and linkage disequilibrium for IL-10RA and IL-22. Our results indicate that genetic variation in these genes may play a modulatory role in the outcome of hepatitis C infection.